Radius and Diameter of Some Family of SV Neutrosophic Graphs - Y.Srinivasa Rao, D.Venkata Lakshmi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the present article, we deduce a characterization of SVN eccentric vertex. The concepts of SVN graph are examined. Also we obtained some definitions SVN on a vertex like SVN eccentric vertex, SVN radius, SVN diameter, SVN centered and SVN periphery. We derive some important results based on these SVN radius, diameter, center and periphery.